The Influence of Instagram on Fomo Syndrome (Fear of Missing Out) - Shelly Dike Ananda; Luthfia Amira Khadijah; Fransiska Lissa; Ageng Triyono (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2023)
FoMO (Fear of Missing Out) which means fear of being left behind in any case, for example the newer trends and fashions. Someone who has FoMo syndrome tends not to be himself, and it's easy to follow others. One of the reasons is the frequent access to Instagram social media. Therefore, the purpose of this study was to determine whether there is influence of Instagram social media on FoMo syndrome. This type of research is quantitative research with survey methods. The population in this study were all students of the Faculty of Communication and Multimedia, Mercu Buana University Yogyakarta class of 2021. The instruments used were a questionnaire on the use of social media and the FoMO syndrome. The data analysis used is the Pearson Product Moment correlation to determine the relationship between Instagram social media use and FoMO syndrome, and simple linear regression analysis to determine whether there is an influence of Instagram social media on FoMO syndrome. The results showed that there was a strong positive relationship between Instagram social media and student FoMO syndrome. Furthermore, there is a 60% influence between the use of social media on FoMO syndrome in college students. So that the other 40% is influenced by other variables not examined.